Efektivitas Pelaksanaan Pembelajaran Jarak Jauh pada Mata Pelajaran Kimia selama Pandemi Covid-19 - Ananda Mutiara Aulia; Dedi Irwandi; Luki Yunita (Chemistry Education Study Program Sriwijaya University, 2023)
The World Health Organization (WHO), on March 11, 2020, declared Covid-19 as a pandemic that has not only severely affected humankind but also frozen almost all areas of life on the planet. Since then, the Covid-19 pandemic has caused the most considerable turmoil in the education sector. To ensure the education process continues, the Minsitry of Education and Culture of the Republic of Indonesia responded to this situation by closing schools and rolling out distance learning options for their students. Thus, this study aims to determine the effectiveness of Chemistry distance learning during the Covid-19 pandemic. The method employed in this study is descriptive quantitative using an online questionnaire as the data collection tool. A total of 108 MIPA students at SMAN 1 Cikarang Pusat were selected using a probability sampling technique. The results of this study in the form of student response analysis obtained 85% on the overall aspects of the effectiveness of Chemistry distance learning with very effective criteria.